CARIES EXPERIENCE IN CHILDREN WITH SEVERE EARLY CHILDHOOD CARIES - Ioana-Andreea Stanciu; Cristina-Crenguța Albu; Mihaela Tănase; Arina Vinereanu; Aneta Munteanu (Romanian Society of Oral Rehabilitation, 2024)
Aim: To assess the distribution and severity of dental caries and association with demographic factors in children with severe early childhood caries (S-ECC) in a university pedodontic clinic. Methods: A retrospective observational descriptive study was performed, analyzing the dental files of 165 Caucasian patients (96 boys), with mean age=3.79±10.15 years, diagnosed with S-ECC within the Pedodontics Department, Carol Davila University, Bucharest, during 2007- 2017. Caries experience indices (dmft/s, SiC), restorative index (RI) and distribution and severity of carious lesions were assessed. Statistical analysis was performed with SPSS 20.0 program, using ANOVA and t-test (p=0.05). Results: Caries experience indices: dmft=9.16±4.18; dmfs=20.66±10.94; dmftboys=8.98±4.14; dmftgirls=9.42±4.26 (p=0.5079); dmfsboys=20.31±10.66; dmfsgirls=21.14±11.39 (p=0.6351); dmftcapital=9.06±4.08; dmftsuburbs=9.51±4.57 (p=0.5909); dmfscapital=20.43±11.61; dmfssuburbs=21.46±8.34 (p=0.5492); SiC=14.02±2.80; SiCboys=13.81±2.78, and SiCgirls=14.22±3.00 (p=0.6129). RI value was 0.80%. From 3163 studied teeth, 1651 (52.20%) were caries-free, 1487 (47.01%) had caries lesions, 13 (0.41%) were missing, and 12 (0.38%) were filled. The upper incisors (37.26%), followed by the first molar teeth (27.44%) were the most frequently affected teeth. 135 (81.82%) children had at least one complicated caries, while 30 (18.18%) had only uncomplicated ones. 35 (21.21%) children had caries on primary teeth, including the lower front teeth and 130 (78.79%) had caries on primary teeth, except for the lower front teeth; Conclusion: The children examined showed high values of decayed teeth/surfaces, most of them had complicated caries and a very small percentage had treated lesions and extracted teeth. It is important to develop preventive programs for toddlers and preschool children, as well as regular dental check-ups established as close as possible to the eruption of the first primary tooth in order to avoid the onset of this pattern of caries.